Cookery of the cheaper cuts of beef - Cunningham, Margaret Ruth; Hull, Flora May (My University, 1907)
Introduction: The subject of the cookery of the cheaper cuts of meats is one which is probably very little thought of, and much less studied. One concludes that unless he can pay a good price and secure the popular or choice cuts, that he must go without meat or limit it to a very great extent in his dietary. This conclusion is erroneous because the cheaper meats are as nutritious and often more highly flavored than some of the more expensive cuts. It is true that the most of the cheaper meats require a greater length of time for cooking. This is no factor against them in winter because as a rule the fire is kept up most of the day, and it is no waste of fuel to cook the meat a long time; even in summer there are usually several days of each week when long fires are used. Since the invention of the fireless cooker, there is no reason why every one should not own one as they are of little or no expense. With this cooker the extra cost and inconvenience of keeping up a fire on a summer day is dispensed with. If, then, we can cook cheap meat both winter and summer without extra expense for fuel, and since the meat is as nutritious and often more highly flavored, does it not pay to give a little study to the ways to prepare the cheaper cuts to take the place of high priced, but no more nutritious cuts? "Many people cannot afford to buy the expensive meats for every day use, and, having the false idea that the cheaper pieces are undesirable, they deprive themselves of much needed proteid; or if they buy meat they must lessen the cost by going without some other necessary article of diet. In either case the body is not properly nourished. A bulletin on Scientific Research, in treating the subject of errors in food economy, states that…
Citation: Cunningham, Margaret Ruth and Hull, Flora May. Cookery of the cheaper cuts of beef. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Beef Cuts; Cooking Beef; Beef Quality; Theses